Kualitas Pelayanan Administrasi Pendidikan di UPTD Dinas Pendidikan Kecamatan Porong Kabupaten Sidoarjo - Kholipatun Kholipatun; Isnaini Rodiyah (Universitas Muhammadiyah Sidoarjo, 2014)
The purpose of this study to analyze and describe the quality of educational administration services as well as to describe supporting and inhibiting factors that affect towards quality of educational administration services in Education Department, Porong Subdistrict. In this study, researchers used a descriptive qualitative method. The results showed that educational administration services in Education Department, Porong Subdistrict had good quality. This is supported by good services from officer. In addition, they provide services prima like fast, responsive, accommodative, innovative, productive and economic. In addition, there were 5 elements in this services, namely reliability, responsiveness, assurance, empathy, and tangible. While supporting and inhibiting factors could affect the service itself, namely: resource officers, public awareness, and facilities.